2019
DOI: 10.1093/cid/ciz194
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Chest Computed Tomography for Early Diagnosis of Invasive Pulmonary Aspergillosis in Hemato-oncological Patients: A Prospective Cohort Study

Abstract: Invasive pulmonary aspergillosis (IPA) has dire consequences in hemato-oncological patients. We report our experience with performing routine baseline chest computed tomography for early diagnosis of IPA. We found high rates of proven or probable IPA diagnosed on admission among patients with newly diagnosed acute myeloid leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 7 publications
3
26
0
Order By: Relevance
“…The median estimated IPA rates appeared to be higher with BCT in this survey, a finding that is in line with previous single center studies, but also underlying relatively small sample size and comprising the inherent bias of diagnosing more IPA episodes than without BCT [14,15]. The higher IPA rate suggest BCT as being likely beneficial for early diagnosis, also if asymptomatic.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The median estimated IPA rates appeared to be higher with BCT in this survey, a finding that is in line with previous single center studies, but also underlying relatively small sample size and comprising the inherent bias of diagnosing more IPA episodes than without BCT [14,15]. The higher IPA rate suggest BCT as being likely beneficial for early diagnosis, also if asymptomatic.…”
Section: Discussionsupporting
confidence: 89%
“…BCT was defined as the performance of a CT scan upon admission or at diagnosis of the above-mentioned underlying conditions according to the two above-mentioned studies [14,15]. These two groups may overlap.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No baseline study has been performed to assess the incidence of this synchronous process fully. In a single-center study, Bitterman et al [ 11 ] found that 5% (15 of 295) of high-risk HM patients were diagnosed with invasive pulmonary aspergillosis (IPA) on admission baseline chest computed tomography (CT), with an additional 9.8% diagnosed later during hospitalization. These 15 patients were older and more likely to have a new HM (11 of 15) compared with those who developed IPA at a later point [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Screening for presence of IMI in at‐risk patients upon admission and prior to chemotherapy could be another area of application for the mould‐reactive lymphocyte assay. Besides enabling initiation of earliest possible treatment even before signs and symptoms of IMI are present, this could allow further insight into prevalence of unapparent IMI in at‐risk patients …”
Section: Discussionmentioning
confidence: 99%